2000
DOI: 10.1143/jjap.39.7164
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Dynamics of the Eco RI Enzyme using Stretched DNA: its Application to In Situ Sliding Assay and Optical DNA Mapping

Abstract: The Eco RI enzyme is a nanomachine responsible for gene integrity in cells, and has a sensor that discriminates its specific binding sequence on DNA (GAATTC) from flanking nonspecific sequences. We applied this sequence sensing ability to microscopic DNA mapping. Visible measurement of positions of the GAATTC sequence was accomplished with fluorescently labeled Eco RI and DNA that was stretched by dielectrophoresis and suspended above a glass surface. Statistics showed that Eco RI molecules were trapped at par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Dielectrophoretic forces have been used to separate and manipulate cells, 2,11 bacteria, 12,13 viruses, 14 and submicron latex spheres. 5,15,16 Recently the dielectrophoretic manipulation of DNA molecules has led to applications such as the concentration of DNA molecules, [17][18][19] DNA-protein interaction studies, 20,21 and molecular surgery of DNA. 22 However, a detailed understanding of the behavior of surface-immobilized DNA molecules when exposed to high frequency ac electric fields, and in particular the orientation and elongation of DNA as a result of dielectrophoretic force and torque, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectrophoretic forces have been used to separate and manipulate cells, 2,11 bacteria, 12,13 viruses, 14 and submicron latex spheres. 5,15,16 Recently the dielectrophoretic manipulation of DNA molecules has led to applications such as the concentration of DNA molecules, [17][18][19] DNA-protein interaction studies, 20,21 and molecular surgery of DNA. 22 However, a detailed understanding of the behavior of surface-immobilized DNA molecules when exposed to high frequency ac electric fields, and in particular the orientation and elongation of DNA as a result of dielectrophoretic force and torque, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Kabata et al [46] have directly observed fluorescently labeled EcoRI proteins sliding under convective flow along electrostretched DNA molecules held between electrodes. In these experiments, sliding along the DNA was distinguished from simple convection in the flow by a change in direction of the motion of the stained proteins when they encountered the DNA molecules.…”
Section: Electrostretchingmentioning
confidence: 99%
“…Therefore, while direct DEP of molecular species in solution may usefully be employed for collecting molecules and, at a stretch, for discriminating between different classes of molecules, it does not offer the exquisite sequence-and structure-specific discrimation that is the basis for molecular diagnostics using DNA and proteins. Nevertheless, DEP collection and manipulation of DNA has been demonstrated some 15 years ago by Washizu [102]- [104] and more recently by Austin et al [105] and, as with other ac electrokinetic techniques, the method has the advantage that it is electrically controllable.…”
Section: A Direct Molecular Trappingmentioning
confidence: 99%